Livelihood Vulnerability and Resilience of Rice Farmers in Flood- and Pest-Affected Areas of Karawang Regency, West Java - Fatimah Azzahra; Siti Mariyani; Ana Melani; I Ketut Manu Mahatmayana; Ratna Mufidah; Hitomi Nakayama (Sodality: Jurnal Sosiologi Pedesaan, 2026)
Despite Karawang Regency’s strategic role as a major agricultural production center in West Java, recurring pest infestations and flooding have increasingly undermined farmers’ livelihoods. On the other hand, empirical studies examining livelihood resilience at the household level remain limited, particularly within a sustainable livelihood framework. This research addresses this gap by analyzing the resilience of agricultural livelihoods in Kutawaluya District using a mixed-methods approach. Quantitative data were collected from 55 farming households affected by pest attacks, plant diseases, flooding, and drought, and were complemented by qualitative insights to enrich contextual understanding. Livelihood resilience was assessed using the Livelihood Vulnerability Index (LVI) across key livelihood assets. The results indicate that the ecological dimension exhibits the highest vulnerability, with an LVI value of 0.9, reflecting severe exposure to environmental stressors. However, strong social capital among farming households emerges as a critical mitigating factor that enhances resilience under precarious conditions. This study contributes to the livelihood resilience theory by demonstrating the compensatory role of social capital in contexts of high ecological vulnerability. Practically, the findings provide evidence-based guidance for policymakers and extension services to strengthen social networks and collective action as part of sustainable livelihood strategies in flood- and pest-prone agricultural regions.